2002
DOI: 10.1197/aemj.9.12.1373
|View full text |Cite
|
Sign up to set email alerts
|

End‐tidal Carbon Dioxide Predicts the Presence and Severity of Acidosis in Children with Diabetes

Abstract: Background: Patients with diabetic ketoacidosis (DKA) hyperventilate, lowering their alveolar (PACO 2 ) and arterial carbon dioxide (PaCO 2 ). This ventilatory response lessens the severity of their acidemia in a predictable way. Because end-tidal CO 2 (ETCO 2 ) closely approximates PaCO 2 , measured ETCO 2 levels should allow for predictions about the presence and severity of acidosis in diabetic patients. Objectives: 1) To evaluate the relationship between measured serum bicarbonate (HCO 3 ) and ETCO 2 measu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
18
0
1

Year Published

2005
2005
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 36 publications
(20 citation statements)
references
References 11 publications
1
18
0
1
Order By: Relevance
“…Prior studies have examined the utility of ETCO2 to assess acidosis [7][8][9], pre-hospital trauma [4], and ventilation during procedural sedation [10]. Given our limited sample size, we did not search for the optimal thresholds, instead we relied upon previously defined cut-offs.…”
Section: Discussionmentioning
confidence: 99%
“…Prior studies have examined the utility of ETCO2 to assess acidosis [7][8][9], pre-hospital trauma [4], and ventilation during procedural sedation [10]. Given our limited sample size, we did not search for the optimal thresholds, instead we relied upon previously defined cut-offs.…”
Section: Discussionmentioning
confidence: 99%
“…Therefore, it is also helpful in managing conditions such as diabetic ketoacidosis and dehydration. 3,4 Fearon and Steele 3 demonstrated a linear relationship between ETCO 2 measurements and serum bicarbonate levels in children with diabetes. ETCO 2 was shown to correlate with the severity of metabolic acidosis and thus acted as a predictor of diabetic ketoacidosis in comparison to hyperglycemia.…”
Section: Discussionmentioning
confidence: 96%
“…2 Recent studies have also used it to measure metabolic disturbances. 3,4 It has been shown, however, that continuous ETCO 2 monitoring is underutilized by physicians in pediatric and adult intensive care units abroad and physicians in adult emergency departments and emergency medical service personnel in the United States. 5Y8 This is the first study to investigate how ETCO 2 monitoring is being used by pediatric emergency medicine (PEM) physicians.…”
mentioning
confidence: 98%
“…Using the relationship between PaCO 2 and PetCO 2 , a recent study [46] showed a linear relationship between PetCO 2 and serum bicarbonate with a sensitivity of 0.83 and specificity of 1.0 in patients with diabetic ketoacidosis. PetCO 2 is a helpful noninvasive adjunct for monitoring critically ill patients and for guiding therapy.…”
Section: End-tidal Carbon Dioxide Monitoringmentioning
confidence: 99%